EFFECT OF COMMUNICATION AND COORDINATION ON EMPLOYEE PERFORMANCE AT CV. AFIF KING TAMBAK DELI SERDANG - Purnama Sari, Dian (RADJA PUBLIKA, 2021)
This study aims to determine whether communication and coordination both partially and simultaneously have a significant effect on employee performance at CV. Afif Raja Tambak Deli Serdang and how much influence he had. The method used in this study is a quantitative method with several tests, namely reliability analysis, classical assumption deviation test and linear regression. Based on the results of the primary data regression which was processed using SPSS 20, the following multiple linear regression equation was obtained: Y = 0.518 + 0.669 X1 + 0.327 X2. Partially, the communication variable (X1) has a significant effect on employee performance (Y) at CV. Afif Raja Tambak Deli Serdang. This means that the hypothesis in this study is accepted, as evidenced by the value of t count > t table (7.749 > 2.052). While the coordination variable (X2) has a significant effect on employee performance (Y) at CV. Afif Raja Tambak Deli Serdang. This means that the hypothesis in this study is accepted, as evidenced by the value of t count > t table (3.389 > 2.052). Simultaneously, the variables of communication (X1) and coordination (X2) have a significant effect on employee performance (Y) at CV. Afif Raja Tambak Deli Serdang. This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (340.584 > 3.35). Communication variables (X1) and coordination (X2) are able to contribute to the influence of employee performance variables at CV. Afif Raja Tambak Deli Serdang (Y) is 96.2% while the remaining 3.8% is influenced by other variables not examined in this study. From the conclusion above, The author suggests that employees and leaders should further improve and maintain existing coordination so that existing cooperation is more awake. Employees should work sincerely so that there are no company goals and employee needs are met by CV. Afif Raja Tambak Deli Serdang.